(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
Despite the recognized important role of strategic orientation in achieving company's business goals and overall firm performance, the manufacturing firms has not leveraged on it to enhanced their performance. Thus, this study examined the effect of strategic orientation on the performance of manufacturing firms in Abuja, Nigeria. Specifically, the study examined the effect of customer orientation and technological orientation on the performance of manufacturing firms, the study was anchored on Dynamic Capability Theory. Survey research design was adopted, the population of the study were one hundred and twenty-nine (129) owner/mangers of the selected manufacturing firms registered with (CAC) in Abuja with a minimum of five years in operation. Primary data with the aids of questionnaire on five-point likert scale was used in the study. The hypotheses of the study were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). The result revealed that that customer orientation has a significant negative effect on performance; the study also found that technological orientation has a significant positive effect on the performance of manufacturing firms in Abuja. The study concluded that strategic orientation has a significant effect on the performance of manufacturing firms in Abuja. Based on the findings the study recommended that manufacturing firms in Abuja should implement robust customer feedback system and prioritizing customer needs; this can be ensured by establishing digital platforms and market survey to gather real-time insight on customers’ needs and preferences. They should also continuously invest in advanced technologies, and encourage a company-wide culture that promotes technological innovation which can be achieved through regular training and collaboration with tech partners.